Tales from Shakespeare - Lamb, Charles, 1775-1834; Lamb, Mary, 1764-1847 (Salt Lake City, UT : Project Gutenberg, 1998)
"Tales from Shakespeare" by Charles Lamb and Mary Lamb is a collection of retellings of some of William Shakespeare's most famous plays, written in the early 19th century. The book aims to serve as an introduction for young readers to the works of Shakespeare, blending his original language with accessible prose, while carefully selecting words to maintain the beauty of the English language. The opening of the collection includes a preface explaining the purpose and structure of the abridged tales, emphasizing that they seek to make Shakespeare$1 (Bs stories easier to understand for young audiences. It then begins with "The Tempest," introducing characters such as Prospero, a duke turned sorcerer, and his daughter Miranda, who live in isolation on an enchanted island. The narrative highlights Prospero's magical abilities and his plot to regain his dukedom, showcasing themes of love, betrayal, and reconciliation as various shipwrecked characters interact in this strange new world, all leading to profound discoveries about identity and forgiveness. (This is an automatically generated summary.)s
Release date is 1998-04-01
Dianne Bean and David Widger
Keywords: Shakespeare, William, 1564-1616 -- Adaptations; Shakespeare, William, 1564-1616 -- Stories, plots, etc. -- Juvenile literature